A study on corrosion failure of the circulation line with valve openings in atmospheric tower based on CFD. (November 2022) - Quan, Jianxun; Liu, Xiaofei; Wang, Chunyu; Gu, Yong; Wang, Chao; Jin, Haozhe
Highlights: Process analysis and CFD method were used to analyze the failure causes of the reducing pipe. The failure was caused by the erosion after corrosive solution dissolved of HCl and H2 S. The opening of gate valve can increase corrosion risk of pipe bottom wall. Abstract: The perforation failure occurs frequently in the pipeline system of the atmospheric distillation tower. In this paper, the methods of technological process and computational fluid dynamic (CFD) were used to reveal the failure reason of the reducing pipe and provide theoretical guidance. The results of X-ray diffraction analysis shows that the corrosion products of circulation line reducing pipe is FeS and other corrosive substances. The corrosion mechanism was studied and the process was described. Besides, it was found that the valve in the circulation line was not fully opened in the early maintenance. The CFD result shows that the increase of the valve opening will aggravate the corrosion risk of the reducing pipe bottom wall.